Lower back pain and associated factors among weavers working in Bahir Dar City, Northwest Ethiopia: A cross-sectional study - Zinabu, Fiseha Sefiwu; Getie, Kefale; Takele, Mihret Dejen; Chanie, Samuel Teferi; Abich, Yohannes; Shibabaw, Yadelew Yimer; Kibret, Alemu Kassaw (Frontiers in Public Health, 2024)
The prevalence of work-related musculoskeletal disorders is common among informal small-scale enterprises particularly lower back pain is a common occupational health problem in many industries including weaving factories. Lower back pain had a detrimental effect on the function, performance, and production of weavers. However, there is little information on the prevalence and associated factors of low back pain among weavers of Bahir Dar city as well as in the countrywide. Therefore, this study aimed to assess the prevalence and associated factors of lower back pain among weavers working in Bahir Dar City.Method: A multi-centered institutional-based cross-sectional study was carried out on 403 weavers in Bahirdar City, Ethiopia from April to May 2023 using a structured face-to-face interview questionnaire. Samples were proportionally allocated to each institution and study participants were selected by simple random sampling technique. Variables with a P-value less than 0.25 in the bivariate logistic regression were taken into multivariable logistic regression analysis after model fitness was checked. In the multivariable logistic regression analysis, adjusted odds ratio (AOR) with a 95% confidence interval(CI) and a p-value of less than 0.05 were used to identify the associated factors of lower back pain among weavers.Result: This study revealed that the overall annual prevalence of lower back pain was 63.5% (95% CI=58.8-68.5). Longer working hours [AOR=2.580, ( CI=1.517-4.384)], lack of back support [AOR= 1.938, (CI= 2.089-3.449)], repetitive movement of the back during weaving [AOR=5.940, (CI=2.709-13.02)], awkward posture [AOR=2.915, (CI= 1.677-5.065), static working postural [AOR=4.505, (CI=2.298-8.831)], and job stress [AOR=3.306, (CI=1.896-5.765)] were significantly associated with lower back pain among weavers.The prevalence of lower back pain among weavers was common. Working longer hours, lack of back support, repetitive movement of the back, awkward posture, static posture, and job stress were significantly associated with lower back among weavers. We advise quick interventions on weavers to modify the sitting support, weaving less than eight hours per day, changing positions every two hours, reducing job-related stress, and minimizing task repetition to enhance working conditions and minimize the occurrence of lower back pain.